1999
DOI: 10.1210/mend.13.3.0242
|View full text |Cite
|
Sign up to set email alerts
|

Action of Insulin Receptor Substrate-3 (IRS-3) and IRS-4 to Stimulate Translocation of GLUT4 in Rat Adipose Cells

Abstract: The insulin receptor initiates insulin action by phosphorylating multiple intracellular substrates. Previously, we have demonstrated that insulin receptor substrates (IRS)-1 and -2 can mediate insulin's action to promote translocation of GLUT4 glucose transporters to the cell surface in rat adipose cells. Although IRS-1, -2, and -4 are similar in overall structure, IRS-3 is approximately 50% shorter and differs with respect to sites of tyrosine phosphorylation. Nevertheless, as demonstrated in this study, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
6

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 45 publications
3
28
0
6
Order By: Relevance
“…This slight mRNA inhibition was also observed in the current study, especially in cells under insulin treatment, suggesting a direct relationship between VC and insulin resistance/sensitivity pathways. It has been described earlier that Irs3 overexpression induces higher translocation of GLUT4 proteins to the membranes of rat adipose cells, and also that mutant and non-functional IRS3 inhibits insulin action (Zhou et al 1999). Consequently, down-regulation of this gene could have contributed to the observed glucose uptake VC-mediated inhibition.…”
Section: Discussionmentioning
confidence: 91%
“…This slight mRNA inhibition was also observed in the current study, especially in cells under insulin treatment, suggesting a direct relationship between VC and insulin resistance/sensitivity pathways. It has been described earlier that Irs3 overexpression induces higher translocation of GLUT4 proteins to the membranes of rat adipose cells, and also that mutant and non-functional IRS3 inhibits insulin action (Zhou et al 1999). Consequently, down-regulation of this gene could have contributed to the observed glucose uptake VC-mediated inhibition.…”
Section: Discussionmentioning
confidence: 91%
“…It is possible, however, that PI 3-kinase activation mediated via IRS-3 in the PM fraction contributes to the translocation of GLUT4. Indeed, increased translocation of GLUT4 has been demonstrated in rat adipose cells that overexpress IRS-3 (43). A more recent report, however, has shown that insulin-stimulated glucose transport in adipocytes from IRS-3-null mice is the same as in wild-type mice (44).…”
Section: Discussionmentioning
confidence: 97%
“…IRS-3 undergoes tyrosine phosphorylation in rodent adipocytes, leading to activation of phosphatidylinositol 3-kinase, among other possible downstream signalling pathways [4,13,14,19,20,21]. The human and mouse IRS-1 and IRS-2 proteins are 89% and 83% identical respectively [22].…”
Section: Discussionmentioning
confidence: 99%